Risk-tailored starting age of breast cancer screening based on women's reproductive profile: a nationwide cohort study - Mukama, Trasias; Fallah, Mahdi; Tian, Yu; Sundquist, Kristina; Sundquist, Jan; Brenner, Hermann; Kharazmi, Elham (European journal of cancer, 2020)
Abstract: Background. Although reproductive history is recognised to affect the risk of breast cancer, current breast cancer screening guidelines do not consider risk differences by this important factor. As there is a need for an earlier screening in women at increased risk of breast cancer, we provided evidence-based risk-adapted starting age of screening based on different reproductive profiles.Material and methods. We conducted a nationwide cohort study including 5,099,172 Swedish women born after 1931. Records of study participants in Swedish Cancer Registry, Multi-generation Register, Cause of Death Register, and national censuses (follow-up, 1958-2015) have been linked. We used 10-year cumulative risk of breast cancer curves to determine the age at which women with different reproductive factors attained the risk level at which breast screening is usually recommended. Results:The 10-year cumulative risk of breast cancer at age 40, 45 and 50 years in the general population, at which current screening guidelines recommend screening was calculated. We found that women with various reproductive factors (defined by parity and age at first birth) obtained this level of risk at different ages. The difference was between nine years later and three years earlier. Conclusions: This study provides the age at which women with particular reproductive profile could start risk-adapted breast cancer screening. This supplies novel information for clinicians and women about when to start breast cancer screening and is an important step towards a personalised screening.
Published online: 21 November 2019
Gesehen am 23.04.2020